PENGARUH PERBANDINGAN TERIGU DAN BEKATUL BERAS MERAH TERHADAP KARAKTERISTIK MIE KERING - Budihartini, Ni Komang Sri; Permana, I Dewa Gede Mayun; Ina, Putu Timur (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2018)
The purpose of study were to find the optimum ratio of wheat flour with red rice bran to produce the best characteristics of dry noodle. The Completely Randomized Design was used in the research with treatment that is the ratio of flour with red rice bran which consist of 6 levels: 100%:0%; 95%:5%; 90%:10%; 85%:15%; 80%:20%; 75%:25%. The treatment was repeated 3 times to obtain 18 units of experiment. The data obtained were analyzed by variance and if the treatment had an effect on the observed variable then continued with Duncan Multiple Range Test (DMRT) test. The ratio of flour to red rice bran significantly influenced moisture, ash , fat, protein, carbohydrate, c urde fiber content , inhibitor concentration (IC50), water absorption, color (scoring test ), flavor (hedonic test), texture (hedonic test and scoring), taste (hedonic test) as well as overall acceptance (hedonic test) dry noodle . The ratio of wheat flour and red rice bran flour   ( 8 0 %: 20 % ) produces dry noodle with the best characteristics namely: 10.67 % moisture content, ash content  2.91 %, 1.09 % fat content, 13.52 % protein content, 71.80 % carbohydrate content, 4.15 % crude fiber content, IC50 149.35 mg/ml, water absorption 223.23%, dark red color and rather liked color , rather liked flavor, elastic and rather liked texture, rather liked taste and rather liked overall acceptability.